Abs. Issue 1 (November 2015) - Grigorieva, E.; Karbyshev, M.; Volkomorov, V.; Kremmer, E.; Huber, A.; Mitrofanova, I.; Zavyalova, M.; Kaigorodova, E.; Kzhyshkowska, J.; Cherdyntseva, N.
Abstract : Background: Transmembrane prostate androgen-induced protein 1 (TMEPAI) is a membrane protein that has attracted significant attention of many researchers its involvement in TGF- β signaling pathway which involved in malignant transformation and metastatic tumor progression. We investigated the TMEPAI expression level in gastric adenocarcinomas in comparison to non-tumor mucosa samples and determined its potential prognostic significance. Materials and methods: Fresh and paraffin-embedded gastric adenocarcinoma samples and paired adjacent normal tissues were collected from gastric cancer patients. Evaluation of the PMEPA 1 gene expression was carried out using RT-PCR. For evaluation of TMEPAI protein expression, monoclonal antibodies (mAbs) were developed by using hybridoma techniques. Specificity of prepared monoclonal antibodies against recombinant TMEPAI and evaluation of its expression in the clinical samples using selected mAbs were performed using immunoblotting and immunohistochemistry. Results: We have identified more than two-fold increase in gene expression of PMEPA1 in tumor tissue in 44% of patients. The monoclonal antibodies have shown the capacity to specifically recognize the recombinant TMEPAI in HEK293T cell lysates. We also evaluate the ability of the selected antibodies to recognize the target protein in fixed cells by immunocytochemistry. The evaluation of TMEPAI in adenocarcinoma samples collected from gastric cancer patients revealed decreased protein expression. We have observed pronounced expression of TMEPAI in normal gastric epithelial cells, while tumor cells from gastric adenomas and adenocarcinomas samples were mostly negative for target protein expression. We found that gastric epithelium cells lose the TMEPAI expression concurrent with severe dysplasia. Conclusion: Apparently, the TMEPAI may be a potential biomarker of malignant transformation risk of the stomach epithelium. The presented study was financially supported by Grants from theRussian Fund for Basic Research (14-04-31500 ) and Tomsk State University Competitiveness Improvement Program.